The association between satisfaction with husband's participation in housework and suicidal ideation among married working women in Korea. - Lee, Sang Ah; Park, Eun-Cheol; Ju, Yeong Jun; Han, Kyu-Tae; Yoon, Hyo Jung; Kim, Tae Hyun (Psychiatry research, 2018)
Although married women are increasingly participating in paid labor, housework remains their primary responsibility. This uneven distribution of housework could have a negative impact on their mental health. In this study, we examined the association between satisfaction with husbands' participation in housework and suicidal ideation in married working women. Data were obtained from 3544 participants of the fourth and fifth waves of the Korean Longitudinal Survey of Women and Families. Satisfaction with husbands' participation in housework was classified as satisfactory, less satisfactory, and dissatisfactory. A generalized estimating equations model was used to examine the association. Those who were dissatisfied with their husbands' participation in housework were 2.65 times more likely to think about suicide than those who were satisfied. Subgroup analysis showed that women with an egalitarian gender ideology or low job dissatisfaction were more likely to think about suicide when they were dissatisfied with their husbands' participation in housework. In conclusion, married working women who were dissatisfied with their husbands' participation in housework are more likely to think about suicide than those who are satisfied. Therefore, fostering an environment of fair distribution of housework is necessary for alleviating their stress from the dual burden of work and family. (Copyright © 2018 Elsevier B.V. All rights reserved.)
Keywords: 2000 à aujourd'hui; 2010-2019; asie; charge mentale; corée du sud; discipline; maternité; médecine; projet charge mentale; psychiatrie; périodes historiques; régions géographiques; santé; santé mentale des femmes mariées; suicide; thématiques

La procréation assistée, comment y voir clair? - Fédération du Québec pour le Planning des naissances (Service aux collectivités de l'UQAM/Fédération du Québec pour le Planning des naissances, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; SAC; discipline; femmes*; maternité; médecine; périodes historiques; recherche en milieux de pratique; recherche partenariale; ressource en ligne; santé; sciences; thématiques

Sur la noblesse et l'excellence du sexe féminin, de sa préminence sur l'autre sexe - Agrippa de Nettesheim, Henir Corneille (De l' indécence aux hommes d'accoucher les femmes et De l' obligation aux mères de nourrir leurs enfants suivi de S'il est des signes qui assurent de la puissance des hommes, autant que le font ceux qui répondent de la sagesse des filles, 1990)
Le texte d'Henri Corneille Agrippa, Discours abrégé sur la noblesse et l'excellence du sexe féminin, de sa prééminence sur l'autre sexe, n'est pas seulement une contribution importante à l'histoire du discours sur la différence des sexes : pris hors contexte, il constitue aussi une divertissante démonstration par l'absurde de l'inadéquation de l'analyse des rapports de sexe en termes de déduction par rapport à des attributs (imaginaires ou réels) qui en constitueraient l'essence. Réédition d'après l'éd. de 1744, dont l'orthographe et la ponctuation ont été modernisés (indication de la préf. de 1990).
Première édition 1537 Donné en lecture cours FEM1000: p.28-31;98-109;111;134-137
Keywords: 1700-1799; approches et analyses; cours; discipline; europe; fem1000; france; histoire; histoire des femmes*; maternité; médecine; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexes; thématiques